Analisis Semiotika Roland Barthes Pada Iklan Pocari Sweat Versi Ramadhan 1442 H - Lukman Hakim; Oktavia Monalisa (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
Advertising is one way that companies use to promote their products or services to the public. The object analyzed in this research is the advertisement for Pocari Sweat version of Ramadhan 1442 H. As a commercial product, Pocari Sweat is not spared from a promotion so that Pocari Sweat makes an advertisement video with the theme of Ramadan. The purpose of this study was to analyze the audio visuals of the Ramadan 1442 H version of the Pocari Sweat advertisement. This study used a descriptive qualitative method using Roland Barthes' semiotic analysis approach. The results of this study indicate that the Ramadan 1442 H version of the Pocari Sweat advertisement intends to improve the company's image by using television advertising media and using rising actresses to become advertisement stars. In addition, this advertisement also intends to promote the product through advertising messages that the Pocari Sweat product is very useful for those who are fasting.